Pembekalan Kewirausahaan Melalui Pelatihan Pembuatan Pot Artistik Berbasis Kain Bekas di Rumah Budaya Sidoarjo - Bramantijo, Bramantijo (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2025)
Training in fabric-based artistic pottery is a form of community service that aims to enhance the artistic and entrepreneurial skills of the community at Rumah Budaya Sidoarjo. This activity uses simple techniques and easily obtainable recycled materials to provide creative business opportunities for housewives and teenagers. This article discusses how mastering simple techniques for making artistic pots from recycled fabric can be an important form of entrepreneurial capital. The community service program consists of structured workshops held several times for art enthusiasts gathered at the Sidoarjo Cultural House. Through these workshops, participants learn to make artistic pots from used fabric and gain knowledge about marketing through social media.